From “Sharp, Wittgenstein, is” to “Wittgenstein is Sharp” - Yebra Lopez, Carlos (Análisis. Revista de investigación filosófica, 2016)
Recensión del libro de John Collins, The Unity of Linguistic Meaning, Oxford: Oxford University Press, 2015.